House of cards. The complete second season [videorecording (DVD)]. - Spacey, Kevin; Wright, Robin, 1966-; Gill, Michael R. ([Publisher not identified], 2014)
Frank prepares for his promotion to Vice President. Doug tries to erase all leads leading him back to him and Frank. Claire fights back against Gillian. Zoe considers working with Frank again.